2019
DOI: 10.1002/humu.23912
|View full text |Cite
|
Sign up to set email alerts
|

Multiplex targeted high‐throughput sequencing in a series of 352 patients with congenital limb malformations

Abstract: Congenital limb malformations (CLM) comprise many conditions affecting limbs and more than 150 associated genes have been reported. Due to this large heterogeneity, a high proportion of patients remains without a molecular diagnosis. In the last two decades, advances in high throughput sequencing have allowed new methodological strategies in clinical practice. Herein, we report the screening of 52 genes/regulatory sequences by multiplex high‐throughput targeted sequencing, in a series of 352 patients affected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(43 citation statements)
references
References 28 publications
1
38
0
4
Order By: Relevance
“…We included only cases harboring biallelic variants in RBM8A . Eight of them were reported previously (Jourdain et al, 2020; Table S1). All patients were referred by clinical geneticists or foetopathologists.…”
Section: Clinical Features Nb Cases (%)mentioning
confidence: 99%
See 1 more Smart Citation
“…We included only cases harboring biallelic variants in RBM8A . Eight of them were reported previously (Jourdain et al, 2020; Table S1). All patients were referred by clinical geneticists or foetopathologists.…”
Section: Clinical Features Nb Cases (%)mentioning
confidence: 99%
“…In 2012, Albers et al resolved the complex inheritance mechanism of TAR syndrome and identified the first two noncoding SNPs of RBM8A implicated in this condition (Albers et al, 2012). With the 5′‐UTR and 3′‐UTR variants characterized in this work, we add to the set of known hypomorphic alleles in TAR syndrome, improving the performance of molecular diagnostic in TAR syndrome close to 73% on the basis of our previously reported unbiased cohort (Jourdain et al, 2020). Nevertheless, the exact mechanism by which these SNPs lead to reduced levels of Y14 remains unclear at the present time.…”
Section: Clinical Features Nb Cases (%)mentioning
confidence: 99%
“…We reported the second variant, c.184A>G;p.(Arg62Gly) in a father and son with SYNS but they also had craniosynostosis, with the son requiring surgical intervention 5 . This same variant was subsequently observed in another patient with SYNS, but no craniosynostosis was reported 6 . Here, we report the third FGF9 variant, c.427A>T;p.(Asn143Tyr) in a young girl with SYNS.…”
Section: Discussionmentioning
confidence: 55%
“…To date, only two heterozygous FGF9 variants have been reported in humans with SYNS3, c.296G>A;p.(Ser99Asn) and c.184A>G;p.(Arg62Gly) 3,5,6 . Here, we report a third variant, located at the same amino acid residue as the Eks mouse mutation.…”
Section: Introductionmentioning
confidence: 67%
See 1 more Smart Citation